Ability of Vegetation Absorption to CO₂ Emissions at the Campus of Universitas Negeri Padang - Indra Yuzandi; Azwir Anhar (Pascasarjana, Universitas Negeri Padang, 2022)
Green Open Space (GOS) is an elongated/lined area and/or clustered, where plants grow, either growing naturally or intentionally planted. Plants or vegetation function as absorbers of Carbon dioxide (CO₂) in the atmosphere and can be absorbed by trees through the process of photosynthesis. For this reason, the purpose of this study was to determine the amount of vegetation, to determine the amount of vegetation absorption of CO₂. This study used the census method by measuring all vegetation stands. For data analysis, calculate the diameter of the tree at chest height (DBH), calculate tree biomass, calculate the estimated carbon stored, and calculating the amount of carbon dioxide absorbed by the vegetation. The results showed that the potential for CO₂ absorption at Padang State University was found to be 1348 tree species. The ability of vegetation to absorb CO₂ is 1,697,812.70 kg/year.